Deregulation of autophagy in postmortem brains of Machado‐Joseph disease patients. Issue 2 (8th December 2017) - Sittler, Annie; Muriel, Marie‐Paule; Marinello, Martina; Brice, Alexis; den Dunnen, Wilfred; Alves, Sandro
Abstract : Autophagy, the major pathway for protein turnover, is critical to maintain cellular homeostasis and has been implicated in neurodegenerative diseases. The aim of this research was to analyze the expression of autophagy markers in postmortem brains from Machado‐Joseph disease (MJD) patients. The expression of autophagy markers in the cerebellum and the oculomotor nucleus from MJD patients and age‐matched controls with no signs of neuropathology was inspected postmortem by immunohistochemistry (IHC) and Western blot. Furthermore, autophagy was examined by means of transmission electron microscopy (TEM). Western blot and IHC revealed nuclear accumulation of misfolded ataxin‐3 (ATXN3) and the presence of ubiquitin‐ and p62‐positive aggregates in MJD patients as compared to controls. Moreover, the autophagic proteins, autophagy‐related gene ( Atg ) protein (ATG)‐7, ATG‐12, ATG16L2 and autophagosomal microtubule‐associated protein light chain 3 (LC3) were significantly increased in MJD brains relative to controls, while beclin‐1 levels were reduced in MJD patients. Increase in the levels of lysosomal‐associated membrane protein 2 (LAMP‐2) and of the endosomal markers (Rab7 and Rab1A) were observed in MJD patients relatively to controls. In addition, these findings were further confirmed by TEM in brain tissue where large vesicles accumulating electron‐dense materials were highly enriched in MJD patients. Postmortem brains with MJD exhibit increased markers of autophagy relative to age‐matched control brains, therefore suggesting strong dysregulation of autophagy that may have an important role in the course of MJD pathogenesis.